Short Message Service Encoding Using the Rivest-Shamir-Adleman Algorithm - Prasetyo, Deny; Widianto, Eko Didik; Indasari, Ike Pratiwi (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
SMS (Short Message Service) is one of the data exchange features in cellphones, including Android smartphones, which are the most widely used smartphone platforms today. However, the security of the SMS is questionable because the message sent must pass through a third party frist, namely SMSC (Short Message Service Center), so that message can be tapped or misused. One of the ways to reduce this risk is to encrypt or keep the original message secret by applying the cryptography algorithm. This research is to develop a system that serves to encrypt and decrypt SMS for Android-based smartphone users. The application is created to encrypt dan decrypt SMS using the Java programming language on Android, that is applied to smartphone integrated with Android Studio and used RSA cryptography algorithm. The application can be used to encrypt and decrypt SMS using the RSA algorithm on the Android-based smartphone. This application can send an SMS with a size of 86 characters and using QR Code to exchange the public key.